Feasibility study of high volume slag as cement replacement for sustainable structural lightweight oil palm shell concrete - Mo, K.H.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Yap, S.P. (Elsevier, 2015)
This paper presents a study on the use of high volume slag as a cement replacement material, and waste oil palm shell (OPS) as a lightweight aggregate to produce a sustainable lightweight concrete (LWC). In order to establish the feasibility of such concrete for structural purposes, the first part of the paper deals with the investigation of the mechanical and bond properties of OPS concrete (OPSC) with varying slag content. The results showed that even though an increase in the slag content led to the reduction in the strength, the OPSC with slag as a 60 cement replacement material exhibited compressive and splitting tensile strengths of 25 and 2.3 MPa, respectively, which exceeded the minimum stipulated strength required for structural LWC. In addition, the use of 60 slag in OPSC showed significant benefits in terms of the reduced cement consumption with improvement in the strength efficiency by almost 2-fold compared to that without slag. On the other hand, it was found that the slag content, albeit as high as a 60 cement replacement level, did not show any significant adverse effects on the normalized bond strength, failure mode, bond strength-slip curve and slip at the ultimate bond strength of the OPSC. To further justify the suitability of the OSPC for structural application, the second part of the paper focuses on the experimental investigation of the flexural behaviour of the actual full-scale reinforced concrete beams. From the flexural tests, it was observed that there were no negative effects on the ultimate moment capacity, failure mode and moment-deflection behaviour of the reinforced concrete beams upon cement replacement with up to 60 slag. Therefore, the utilization of high volume slag-lightweight OPSC could be recommended for actual structural purposes. (C) 2014 Elsevier Ltd. All rights reserved.